Development and characterization of novel 8‐plex DiLeu isobaric labels for quantitative proteomics and peptidomics. (12th May 2015) - Frost, Dustin C.; Greer, Tyler; Xiang, Feng; Liang, Zhidan; Li, Lingjun
<x xml:space="preserve">Abstract</x> Rationale Relative quantification of proteins via their enzymatically digested peptide products determines disease biomarker candidate lists in discovery studies. Isobaric label‐based strategies using TMT and iTRAQ allow for up to 10 samples to be multiplexed in one experiment, but their expense limits their use. The demand for cost‐effective tagging reagents capable of multiplexing many samples led us to develop an 8‐plex version of our isobaric labeling reagent, DiLeu. Methods The original 4‐plex DiLeu reagent was extended to an 8‐plex set by coupling isotopic variants of dimethylated leucine to an alanine balance group designed to offset the increasing mass of the label's reporter group. Tryptic peptides from a single protein digest, a protein mixture digest, and Saccharomyces cerevisiae lysate digest were labeled with 8‐plex DiLeu and analyzed via nanospray liquid chromatography/tandem mass spectrometry (nanoLC/MS2) on a Q‐Exactive Orbitrap mass spectrometer. Characteristics of 8‐plex DiLeu‐labeled peptides, including quantitative accuracy and fragmentation, were examined. Results An 8‐plex set of DiLeu reagents with 1 Da spaced reporters was synthesized at a yield of 36%. The average cost to label eight 100 µg peptide samples was calculated to be approximately 15. Normalized collision energy tests on the Q‐Exactive revealed that a higher‐energy collisional dissociation value of 27 generated the optimum number of high‐quality spectral matches. Relative quantification of DiLeu‐labeled peptides yielded normalized median ratios accurate to within 12% of their expected values. Conclusions Cost‐effective 8‐plex DiLeu reagents can be synthesized and applied to relative peptide and protein quantification. These labels increase the multiplexing capacity of our previous 4‐plex implementation without requiring high‐resolution instrumentation to resolve reporter ion signals. Copyright © 2015 John Wiley & Sons, Ltd.